2012
DOI: 10.1080/13607863.2011.644264
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity, social network type, and depressive symptoms in late life: An analysis of data from the National Social Life, Health and Aging Project

Abstract: Objectives To clarify whether physical activity among older Americans is associated with depressive symptoms, beyond the effects of social network type, physical health and sociodemographic characteristics. Method The analysis used data from a sub-sample, aged 65–85, from the National Social Life, Health and Aging Project (N = 1,349). Hierarchical regressions examined the respective effects of selected network types and extent of engagement in physical activity on depressive symptoms, controlling for physica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
42
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(51 citation statements)
references
References 44 publications
8
42
0
1
Order By: Relevance
“…First, several of our key findings (e.g., regarding physical/functional limitation, medical comorbidity and sleep) were consistent with prior reports (2, 3, 9, 33, 34). Similarly in keeping with prior work (4, 5, 8, 3538), we observed that physical inactivity and smoking were independently related to LLD risk. Second, in an expansion upon the existing literature, we were able to demonstrate dosage effects for most exposures; prior studies typically lacked adequate sample sizes or exposure detail to do so (4, 8, 35, 37, 38).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…First, several of our key findings (e.g., regarding physical/functional limitation, medical comorbidity and sleep) were consistent with prior reports (2, 3, 9, 33, 34). Similarly in keeping with prior work (4, 5, 8, 3538), we observed that physical inactivity and smoking were independently related to LLD risk. Second, in an expansion upon the existing literature, we were able to demonstrate dosage effects for most exposures; prior studies typically lacked adequate sample sizes or exposure detail to do so (4, 8, 35, 37, 38).…”
Section: Discussionsupporting
confidence: 90%
“…Similarly in keeping with prior work (4, 5, 8, 3538), we observed that physical inactivity and smoking were independently related to LLD risk. Second, in an expansion upon the existing literature, we were able to demonstrate dosage effects for most exposures; prior studies typically lacked adequate sample sizes or exposure detail to do so (4, 8, 35, 37, 38). Third, our findings regarding caregiving reinforced the importance of distinguishing types of caregiving activities: in our study, high volume of caregiving to disabled/ill persons was related to higher LLD risk, in line with a cross-sectional study (39), while decreased LLD risk was found for high volume of caregiving to children/grandchildren.…”
Section: Discussionsupporting
confidence: 90%
“…Several cross-sectional studies report positive impact of "real" social networks on cognitive performance (Bassuk et al, 1999;Seeman et al, 2001;Holtzman et al, 2004;Béland et al, 2005), mental illness (Steffens et al, 2005;Voils et al, 2007;van Beek et al, 2011;van der Post et al, 2012), and quality of life (McLaughlin et al, 2010;Sun et al, 2011;Litwin, 2012). Depression has been directly linked to the subjective sense of loneliness and social isolation (Alpass and Neville, 2003;Ayalon and Shiovitz-Ezra, 2011).…”
Section: Relationship Of Sns Use To Mental Healthmentioning
confidence: 99%
“…General population surveys without extensive follow-up attempts and recruitment efforts thus are likely to be systematically missing people with fewer network connections in general and social isolates in particular, thus leading to biases in variables that have been shown to be related to network connections, such as educational and occupational attainment (Paldony and Baron, 1997;Thomas, 2000), political participation (Knoke, 1990), religious attendance (Rote et al, 2013), aggression (Faris and Felmlee, 2011), and physical and mental health (Cornwell et al, 2012;Litwin, 2012). This finding also means that analysts should, where possible, consider the number of network connections to account for this differential nonresponse.…”
Section: Discussionmentioning
confidence: 99%